2001
DOI: 10.1071/ah010096
|View full text |Cite
|
Sign up to set email alerts
|

Health insurance in the Philippines:bold policies and socio-economic realities

Abstract: In 1995, the Philippines government legislated to create an income-rated and predominantly employment-based universal health insurance program over a 15-year The contextThere are several excellent descriptions of the Philippine health system. This section provides a brief summary of the context, drawing mainly on government publications. Health statusThe health status of Filipinos has been improving at an increasing rate over the last 20 years. Inter alia, death rates are declining, and some causes of morbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The limited resources of small hospitals entail lower medical service quality [ 8 ]. Patients will spend more time and money obtaining high-quality services from their ideal medical institutions instead of lower-level hospitals [ 9 , 10 , 11 ]. However, research has revealed that older individuals with noninfectious or chronic diseases can receive sufficient care for their common health needs in primary medical institutions.…”
Section: Introductionmentioning
confidence: 99%
“…The limited resources of small hospitals entail lower medical service quality [ 8 ]. Patients will spend more time and money obtaining high-quality services from their ideal medical institutions instead of lower-level hospitals [ 9 , 10 , 11 ]. However, research has revealed that older individuals with noninfectious or chronic diseases can receive sufficient care for their common health needs in primary medical institutions.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that by 2014 PhilHealth extended subsidized coverage to 14.7 million poor families [8]. Under PhilHealth, women can access delivery services for free or at minimal cost [9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…The NHIP includes a maternity benefit package as part of its coverage [5, 18]. From 1998 until 2003, PhilHealth’s maternal care coverage included reimbursement of health care providers for hospital delivery care (including caesarean births) and other inpatient services, including room and board, diagnostics, medicines, and physician and facility fees.…”
Section: Introductionmentioning
confidence: 99%